Fluorimetric estimation of doxorubicin hydrochloride in plasma, whole blood and tissues of rat - HARIVARDHAN-REDDY, L; MURTHY, RSR (Ars Pharmaceutica (Internet), 2004)
A rapid and sensitive fluorimetric method of estimation of doxorubicin hydrochloride (DH) in whole blood and tissuesof rat was developed. A relatively simpler and sensitive method of estimation in plasma was also developed. Theanalytical parameters were established for both the methods and were compared. The data of relative fluorescenceintensities (RFI) of the methods of estimation of DH in plasma and whole blood indicate high sensitivity of the formermethod. Comparison of RFI values of whole blood and tissues indicate low extraction of DH from whole blood. LowRFI values were observed in case of tissues such as spleen and liver containing blood forming elements, where as, highRFI values were found in case of lung, kidney and heart. Incubation of DH with various concentrations of DNA in vitro,showed a decrease in RFI of DH with time compared to the initial RFI, indicating a strong interaction which isconcentration dependant. High correlation coefficients were observed with lung (0.9996), whole blood (0.9985) andheart (0.9991). The test of intercept performed for the method of estimation of DH in plasma, and the method ofestimation in whole blood and tissues indicate no interference of blank in the estimations. The ‘t’ test performed for theestimated concentrations in recovery studies indicate no significant difference between the added and estimated concentrationsproving the accuracy, and low coefficient of variation (%) and confidence limits indicate the precision of the methods